VERIFIKASI AKUN DATABASE DENGAN PENERAPAN METODE TEMPLATE MATCHING PADA KARATERISTIK WAJAH PERSONAL - Ginting Pebrindanov; Widi Hapsari; Yuan Lukito (Universitas Kristen Duta Wacana, 2015)
The identification of account is a step to keep the important data secure. Nowadays, it can be done by using username and password, but, after see the reality, the using of username and password can’t keep the data secure from the thief. Because of that, the verification of the characteristic of personal face can be a solution to change the using username and password. The method that can be used for verification is template matching.It is implemented in four features of personal face, such as left eye, right eye, nose and lips. The four images of each feature will be extracted with wavelet haar method. The feature extraction will be done during template taking process and verification. The result of this research, the result of verification is determined by two factors, such as the distance between face and web camera is different when the template taking process and the verification process and the diferrent brightness condition when the template taking process and the verification proccess. The threshold value that has been decided is not really able to block the unregistered data. Then the accuracy of the verification activity is still low and it is still not able yet to identify an account well.